ВЛИЯЮЩИЕ ФАКТОРЫ ЭЛЕКТРОМАГНИТНОГО ПОЛЯ СВЧ НА УСКОРЕНИЕ ПРОЦЕССА ЭКСТРАГИРОВАНИЯ - Холмуродова Зубайда Диёровна (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation:This article discusses the preparation of the material for extraction and the influencing factors to speed up the process. These are the process temperature, the size of the material to be extracted, and the magnetization of the solvent. Magnetization increases the dissolving power of the solvent. Technological parameters do not significantly fluctuate from the design of the extractor. Compliance with the technological parameters of extraction increases the yield of extraction oil, and the fodder value of the meal is also preserved. The manufacturer receives high-quality extraction oils and meal.